Sistem Pendukung Keputusan dalam Pemilihan Kulit Sintetis Layak Ekspor pada PT. Yakita Mulia dengan Metode SAW Berbasis Web - Muhammad Raihan Atha; Charles Bronson Harahap (Universitas Methodist Indonesia, 2025)
PT. Yakita Mulia is a company engaged in the production of synthetic leather with a domestic and export market orientation. In the process of determining the quality of synthetic leather suitable for export, the company faces problems at the decision-making stage which is still done manually, thus potentially causing delays, subjectivity, and inaccuracy in the assessment results. Therefore, a decision support system is needed that is able to assist the evaluation process more quickly, accurately, and objectively. This study aims to design and build a web-based decision support system by applying the Simple Additive Weighting (SAW) method. The SAW method was chosen because it has a simple, structured calculation process and is able to provide objective assessment results for each evaluated alternative and can rank alternatives based on predetermined criteria such as material durability, color, texture, elasticity and conformity to export standards. This system allows users to input assessment data, then the calculation results are displayed in the form of a ranking so that it can facilitate the company in determining synthetic leather products that are suitable for export. The implementation results show that this web-based decision support system is able to process data quickly and produce more objective recommendations than the manual process. With this system, the process of selecting synthetic leather suitable for export at PT. Yakita Mulia becomes more efficient, accurate, and supports increasing the company's competitiveness in meeting international market demands.